COLORECTAL CANCER SCREENING STATUS AND ASSOCIATED FACTORS AMONG ADULTS IN CAN THO CITY, VIETNAM - Nguyen Huu Ky Phuong (International Journal of Health Management Review, 2026)
Objective: To describe colorectal cancer (CRC) screening status and identify associated factors among adults aged 45-74 years in Can Tho City, Vietnam. Methods: This analytical cross-sectional study included 600 participants from 12 clusters. Frequencies, proportions, and adjusted odds ratios (aORs) were estimated using multivariable logistic regression with cluster-adjusted standard errors. Results: Overall, 159 participants (26.5%) were up to date with CRC screening. Among those screened, 59.1% had undergone colonoscopy, 30.2% had used FIT/FOBT, and 10.7% had used both methods. Among 441 participants not up to date, the most frequently reported barriers were the absence of a healthcare provider recommendation (56.9%) and the belief that screening was unnecessary without symptoms (37.2%). Age >=60 years, household income >=VND 10 million/month, family history of CRC, an annual health check-up, good screening knowledge, and a healthcare provider recommendation were independently associated with being up to date. Provider recommendation showed the strongest association (aOR=4.91; 95% CI: 2.96-8.12). Conclusion: CRC screening coverage was limited in the study population. Proactive provider counseling and communication that screening should occur before symptoms emerge should be prioritized.